A hybrid multi-reference subband control strategy for active noise control headphones. (August 2022) - Patel, Vinal; Cheer, Jordan
Abstract: Multi-reference feedforward Active Noise Control (ANC) has been shown to provide increased noise mitigation capability in ANC headphones compared to a single reference feedforward controllers, due to the availability of additional time advanced information. Recent studies have also shown that the integration of a single-reference feedforward controller and a feedback controller increases both the noise cancellation bandwidth and system stability, therefore, a corresponding hybrid version of the multi-reference control strategy has been developed and is presented in this paper. The hybrid multi-reference ANC (HMRANC) system is comprised of a multi-reference feedforward control unit acting in conjunction with a feedback ANC system. In addition, to overcome the high computational demand of the hybrid structure, a delayless subband version of the HMRANC system is also presented in this paper. The proposed HMRANC and delayless subband HMRANC headphone systems achieve an improvement of 5–10 dB over the previously proposed hybrid ANC headphone system for different acoustic field scenarios. Moreover, the delayless subband HMRANC headphone system is 40% less computationally demanding then HMRANC and 10% less demanding than HANC headphone systems.